Model Pembelajaran Inklusif Berbasis Hadis dalam Mewujudkan Pendidikan yang Adil dan Setara - Agus Mujiono; Muhid Muhid (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This study aims to analyze the relationship between inclusive education and Hadith values and to formulate a Hadith based inclusive learning model within Islamic education context The research uses a qualitative library approach by analyzing Hadith books and relevant scholarly articles The findings show that equality justice and compassion in inclusive education align with Hadith values on seeking knowledge fairness and mercy Inclusivity in Islam emphasizes not only access but also proportional treatment based on learners needs and humane interaction The study proposes a Hadith based inclusive learning model integrating equality justice and compassion into planning implementation and evaluation processes Furthermore the findings indicate that integrating Hadith values into pedagogy strengthens affective and social dimensions of learners while improving teacher student relationships This approach encourages flexible adaptive and student centered learning practices that accommodate diverse abilities backgrounds and characteristics more effectively Therefore the proposed model is not only theoretically grounded but also practically applicable in contemporary Islamic education which requires fairness inclusivity and sustainability in instructional processes and classroom management Moreover it supports holistic development by linking cognitive emotional and spiritual aspects of learning experiences for all students regardless of their conditions or social backgrounds in diverse educational settings This ensures that inclusive education becomes meaningful transformative and aligned with ethical and religious values in practice for sustainable learning outcomes